2021
DOI: 10.1093/noajnl/vdab071.101
|View full text |Cite
|
Sign up to set email alerts
|

SURG-08. Laser Interstitial Thermal Therapy (LITT) versus Resection in the Treatment of Lesions In or Near the Primary Motor Cortex

Abstract: Introduction Laser interstitial thermal therapy (LITT) is a minimally-invasive treatment option for radiographically-progressive (RP) brain metastases. This study compares the functional outcomes of LITT vs resection (RS) for lesions in or near the primary motor cortex (PMC). Methods Retrospective review was performed of patients treated for PMC lesions by LITT or RS. Functional outcomes were graded relative to pre-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 51 Our unpublished work on LITT near the motor cortex has shown that patients who survive out to 6 months have similar functional outcomes compared to craniotomy, with a trend toward greater benefit in pretreatment steroid responders. 52 …”
Section: Limitations Of Littmentioning
confidence: 99%
“… 51 Our unpublished work on LITT near the motor cortex has shown that patients who survive out to 6 months have similar functional outcomes compared to craniotomy, with a trend toward greater benefit in pretreatment steroid responders. 52 …”
Section: Limitations Of Littmentioning
confidence: 99%